PENDIDIKAN KARAKTER DALAM KAJIAN FILSAFAT NILAI - Ida Rochmawat (STIT Muhammadiyah Paciran Lamongan, 2019)
The main goal of becoming human character education in Indonesia. Character education that proclaimed nationally and massif in all levels of education to this point so that learners have a superior character. The application of character education that has gone on for many years such has been his impact can be felt or is only limited to the theory presented in front of the class and become the motto in schools. In the view of philosophy of value, character education is the cultivation of the values that will be embedded in the inside. In Indonesia, it is character education who wish to apply should be tailored to the purpose of ed ucation nationally with a system of values that already exist in the community. Among the many values that thrive in the community, in fact Indonesia nation already has the basics of value yanag bermsyarakat life ilandasaan, became a nation and a country